2019
DOI: 10.1590/rbz4820180030
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of morphometry effect on race performance in Thoroughbred horses

Abstract: The objective of this study was to determine the effects of morphometric measurements on race performance (m/sec) of Thoroughbred horses. Data of morphometric measurements (withers height, rump height, chest girth, chest width, front chest width, chest depth, neck length, shoulder length, length of withers to rump, rump length, body length, head width, head length, and cannon circumference) were taken from 244 Thoroughbred horses chosen at random. A total of 2888 racing records were considered for race perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In Thoroughbred racehorses, yearling measurements for height at the croup, body length, and girth circumference were found to be correlated with winning percentage in both females and males [19]. However, Paksoy and Ünal [14] found no relationship between the results of morphological measurements and race performance. There have been many fewer studies of the relationship between conformation and performance in racehorses than in riding horses [2,6,7,13,18].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In Thoroughbred racehorses, yearling measurements for height at the croup, body length, and girth circumference were found to be correlated with winning percentage in both females and males [19]. However, Paksoy and Ünal [14] found no relationship between the results of morphological measurements and race performance. There have been many fewer studies of the relationship between conformation and performance in racehorses than in riding horses [2,6,7,13,18].…”
Section: Discussionmentioning
confidence: 88%
“…As shown in Fig. 1, we took the following manual measurements: M1 − height at the withers (HWi), measured from the ground to the withers M2 − height at the back (HBa), measured from the ground to the lowest point of the back M3 − height at the croup (HCr), measured from the ground to the highest point of the tuber sacrale M4 − chest depth (ChD), measured from the highest point of the withers to the lower edge of the sternum (the point behind the posterior edge of the elbow joint) [11] M5 − width of the chest (WCh), measured distance in the front side between the outer sides of the right and left humeri [14] M6 − width of the croup (WCr), measured between the hip joints M7 − width of the waist (WWa), measured between the tuber coxae M8 − girth circumference (GiC), measured circumference of the trunk through the withers and the sternal area M9 − cannon circumference (CaC), measured circumference of the front cannon at the middle M10 − body length (BoL), measured from the point of the shoulder to the midpoint of the distance between the widest part of the stifle and the tail when viewed from the rear, making the measuring tape fit the curve line of the horse's body surface according to Wagner and Tyler [21] The measuring tools included measuring stick (M1−4), caliper (M5−7), and measuring tape (M8−10). During stick measurements, an assistant standing behind the horse made sure that the stick was standing vertically.…”
Section: Conventional Manual Measurementsmentioning
confidence: 99%
“…Depending on breeds, increased maternal age reduces the size of foals until at least 6 months of age (Hintz et al 1979;Klewitz et al 2015;Meirelles et al 2017;Robles 2018). One study on flat racehorses, however, showed that mare age and parity do not influence morphology of the competing adult (Paksoy and Ünal 2019). These differences in growth have been related to reduced plasma IGF-1 concentration in foals from primiparous dams until 4 months of age (Cymbaluk and Laarveld 1996).…”
Section: Fetal and Foal Development (Table 7)mentioning
confidence: 99%
“…The genetic correlations between the linear traits and dressage traits ranged between 0 (walk and head width) and 0.46 (canter angle of shoulder) for Pura Raza Español horses (Sánchez-Guerrero et al, 2017). For Thoroughbred horses, Paksoy and Ünal (2019) estimated correlations varying from 0.12 between height at withers and front chest width to 0.68 between height at withers and height at croup, but the authors concluded that the examined morphometric measurements are not significant to predict race performance for this breed.…”
Section: Introductionmentioning
confidence: 96%